PREDIKSI TINGKAT PENGGUNA NARKOBA DENGAN METODE REGRESI LINEAR BERGANDA BERBASIS WEB - Dahlan Abdullah; Maryana Maryana; muli ani (Teknik Informatika Universitas Malikussaleh, 2021)
Drug cases, are not decreasing from day to day but are increasing, both as dealers, users, sellers, even as dealers. Drug users range from the elderly to the younger generation and children. Based on these problems, the researcher intends to help people related to law and ordinary people by creating an application to predict the level of drug users with multiple linear regression methods. Data on drug users used from 2015 to 2019 were taken at the Aceh Tamiang Police (Polres). To perform calculations using this multiple linear regression method using 619 user data. In its application, the multiple linear regression method results in an equation Y’ = -4,492312 + 1,018444 X1 + 1,181143 X2 where X1 is methamphetamine and X2 is marijuana. If the number of methamphetamine users is 108 and marijuana is 76, it can be predicted that the number of drug users is 195 cases and MAPE is 68.48%.Keyword: drugs, predictions, multiple linear regression.